Efficiency Gains for Rheumatology Consultation Using a Novel Electronic Referral System in a Safety‐Net Health Setting. Issue 8 (August 2015) - Scheibe, Meghan M.; Imboden, John B.; Schmajuk, Gabriela; Margaretten, Mary; Graf, Jonathan D.; Chen, Alice H.; Yelin, Edward H.; Yazdany, Jinoos
<x xml:space="preserve">Abstract</x> Objective Health information technology (HIT) holds promise in increasing access to rheumatologists by improving the quality and efficiency of referrals, but few studies have examined its use for this purpose. We evaluated the use and impact of a novel electronic referral (eReferral) system in rheumatology in a safety‐net health system. Methods We examined eReferrals over 4 years. Our primary outcome was use of preconsultation exchange, defined as back‐and‐forth communication between referring and specialty care providers, facilitating triage of referrals, requests for more information, or resolution of questions without a visit. We calculated the proportion of eReferrals that underwent preconsultation exchange, time to reviewer response, and number of visits scheduled. To increase generalizability, we selected a random sample of eReferrals to undergo additional blinded, adjudicated review to assess agreement on appropriateness for preconsultation exchange. Results Between 2008 and 2012, 2, 383 eReferrals were reviewed and 2, 105 were eligible for analysis. One‐fourth of eReferrals were resolved without a clinic visit. The proportion of eReferrals undergoing preconsultation exchange increased over time (55% in 2008 versus 74% in 2011), and the volume of referrals also steadily increased over time. Reviewer response time averaged between 1 and 4 days. In the random sample of eReferrals that underwent adjudicated review, agreement between reviewers was high (κ = 0.72). Conclusion HIT‐enabled preconsultation exchange was used for a majority of eReferrals and facilitated communication between referring clinicians and rheumatologists. This redesigned system of care allowed for triage of a high number of referrals, with many referrals determined to be appropriate for preconsultation exchange.